Key Metabolite Differences Between Korean Pine (Pinus koraiensis) Seeds With Primary Physiological Dormancy and No-Dormancy - Song, Yuan; Gao, Xiaoye; Wu, Yunjie (Frontiers in Plant Science, 2021)
Pinus Koraiensis seeds have physiological dormancy. Cold stratification releases seed dormancy. The changes in metabolite profiles of dormant seeds and cold stratified seeds during shorter incubation time in a favorable condition for seed germination have been studied. However, a more-long term detection of the changes in metabolites in dormant seeds can identify the real metabolic pathways responsible for dormancy. Metabolite composition was investigated in embryo and megagametophyte of primary physiological dormant seeds (DS) of Pinus Koraiensis collected at 0, 1, 2, 4 and 6 weeks of incubation, and of cold stratified seeds already non-primary physiological dormancy (NDS) sampled at 0 and 1 week of incubation, seed coat rupture stage and radicle protrusion stage. Embryos contained higher levels of most metabolites than megagametophyte. Strong accumulation of most metabolites in DS occurred at 1 and 4 weeks of incubation. A larger reduction in the relative levels of most phosphorylated sugars and amino acids in NDS was found between 1-week-incubation and seed coat rupture stage. The relative levels of metabolites involved in carbohydrate metabolism, especially the pentose phosphate pathway and tricarboxylic acid cycle, were higher in the embryos of 4-weeks-incubated DS, but the relative contents of intermediate metabolites of most amino acid metabolism were lower compared to 1-week-incubated NDS. We suggest that the disturbed carbohydrate metabolism and amino acid metabolism in the embryos of DS after 4 weeks of incubation may be related to primary dormancy. Our study provides information for the better understanding of the mechanism of seed dormancy.